Comparative Analysis of Distributed and Centralized PV Integration in a Distribution Feeder Using DIgSILENT Power Factory - Tamang, Rojan; Bhatt, Anil; Gautam, Rupesh; Ghwachha, Rakesh (KEC Journal of Science and Engineering, 2026)
With the rapid growth of photovoltaic (PV) integration into distribution networks, maintaining voltage stability and minimizing feeder overloading have become significant technical challenges for utilities. This study aims to analyze the impact of distributed and centralized PV system integration on the operational performance of a distribution feeder modeled in DIgSILENT PowerFactory and categorized into four different zones. The network was simulated under two configurations: in the distributed PV system, nine PV plants with different generating capacity were strategically allocated across different buses to represent decentralized generation, while in the centralized PV system, the same total capacity was concentrated at the approximate load center. The feeder’s performance is analyzed at 12 different level of PV penetration from 0 to 50% of total generation (14.11 MW), where the feeder was loaded at 3.34 MW. Through detailed load flow analysis, system performance was evaluated based on line loading, voltage profile, and PV bus characteristics. In the distributed system, the feeder’s minimum loss was at 22% PV penetration with over 63% loss reduction. One the other hand, centralized system had minimum loss at 15% PV penetration with over 50% loss reduction. The large number of lines were operating under heavy overloading condition due to large localized power flow in the centralized system compared to that in distributed system under high level of PV penetration. The voltage profile of the distributed PV system is found to be uniformly improving with the increase in PV injection level. The results indicate that distributed PV integration provides more balanced voltage profiles along the feeder, significantly reducing voltage drops, line loading, and power loss. Conversely, the centralized PV configuration caused noticeable voltage rise near the point of connection and higher upstream line loading. The comparative findings demonstrate that distributed PV systems enhance network efficiency and voltage stability, while centralized PV setups offer simpler control but are more prone to localized overvoltage and uneven power distribution. Study also demonstrate that the hosting capacity of the feeder is more in distributed system. The study provides insights into how optimal PV placement strategies can improve the technical performance and reliability of modern distribution networks.